The Effect of Current Ratio, Return on Asset, and Degree of Operating Leverage on Company Value through Capital Structure in the Listed Companies of the Agricultural Food Product Industry over the Period 2016-2020 - Kumba Digdowiseiso; Niken Winarsih (Budapest International Research and Critics University, 2022)
Company value that can be reflected in financial ratios has a strategic role in investment decisions.The purpose of this study is to produce the latest empirical evidence regarding the effect of Current Ratio, Return on Assets, Degree of Operating Leverage on Firm Value through Capital Structure in Agricultural Food Products Industry Companies on the Indonesia Stock Exchange. The study was conducted on 14 samples of companies using purposive sampling in the 2016-2020 period. The data analysis method uses panel data regression method with Structural Equation Model (SEM) which is processed using statistical software STATA 16. The results of the study show empirical evidence that Current Ratio and Degree of Operating Leverage have a direct positive but not significant effect on Firm Value. Return on Assets and Debt to Equity Ratio have a positive and significant direct effect on Firm Value. Current Ratio, Return on Assets and Degree of Operating Leverage have a direct and significant negative effect on Capital Structure. In contrast, the effect of Current Ratio, Return on Assets, and Degree of Operating Leverage on Firm Value cannot be mediated through Capital Structure.